2023
DOI: 10.1038/s41398-023-02357-x
|View full text |Cite
|
Sign up to set email alerts
|

Chemogenetic rectification of the inhibitory tone onto hippocampal neurons reverts autistic-like traits and normalizes local expression of estrogen receptors in the Ambra1+/- mouse model of female autism

Abstract: Female, but not male, mice with haploinsufficiency for the proautophagic Ambra1 gene show an autistic-like phenotype associated with hippocampal circuits dysfunctions which include loss of parvalbuminergic interneurons (PV-IN), decrease in the inhibition/excitation ratio, and abundance of immature dendritic spines on CA1 pyramidal neurons. Given the paucity of data relating to female autism, we exploit the Ambra1+/− female model to investigate whether rectifying the inhibitory input onto hippocampal principal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Then mice were euthanized (deep anesthesia by pentobarbital (60 mg/kg, i.p.) ( Amiri et al, 2017 ) and considering role of hippocampus in the modulation of autistic symptoms ( Walsh et al, 2022 , Pignataro et al, 2023 ), the hippocampi were dissected on the ice-cold surface and directly placed into liquid nitrogen and then stored at −80 °C for molecular evaluations. The schematic of the study design is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Then mice were euthanized (deep anesthesia by pentobarbital (60 mg/kg, i.p.) ( Amiri et al, 2017 ) and considering role of hippocampus in the modulation of autistic symptoms ( Walsh et al, 2022 , Pignataro et al, 2023 ), the hippocampi were dissected on the ice-cold surface and directly placed into liquid nitrogen and then stored at −80 °C for molecular evaluations. The schematic of the study design is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%